Physical layer aware adaptive network coding schemes for satellite communications. (29th September 2017) - Ghanem, Samah A. M.; Gharsellaoui, Ala Eddine; Tarchi, Daniele; Vanelli Coralli, Alessandro
Summary: Network coding is a technology that provides core benefits to communication services, in terms of reliability, latency, and data rate, by leveraging on a coding structure that reduces the necessity for retransmissions of packets. Satellite communications are one of the potential applications that can leverage on the benefits of network coding due to their challenging fading environments and high round trip times. By introducing physical layer awareness, network coding offers further gains to such communications systems. In this paper, we propose different rate and energy efficient adaptive network coding schemes for time‐variant channels. We compare our proposed physical layer aware adaptive schemes to physical layer nonadaptive network coding schemes for time‐variant channels. The proposed schemes demonstrate that adaptation of packet transmissions based on the channel variations over time, and their corresponding time‐dependent erasures, allows for significant gains in terms of throughput, delay, and energy efficiency. We shed light on the trade‐off between energy efficiency and delay‐throughput gains, demonstrating that conservative adaptive approaches that favor less transmission under high erasures might cause higher delay and less‐throughput gains in comparison to nonconservative approaches that favor more transmissions to account for high erasures. We show that such schemes are robust with regimes of large or small packet sizes; albeit the energy per bit is affected, similar rate and energy gains can be obtained. In turn, we show that the performance gains are driven by the duty cycle of the packets silent transmission and not by the packet size. Abstract : Network coding is a technology that provides core benefits to communication services, in terms of reliability, latency, and data rate, by leveraging on a coding structure that reduces the necessity for retransmissions of packets. Satellite communications are one of the potential applications that can leverage on the benefits of network coding because of their challenging fading environments and high round trip times. In this paper, we propose different rate and energy efficient adaptive network coding schemes for time‐variant channels.